2021
DOI: 10.3389/fonc.2020.588360
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Long Non-Coding RNA ELFN1-AS1 Promoted Colon Cancer Cell Growth and Migration via the miR-191-5p/Special AT-Rich Sequence-Binding Protein 1 Axis

Abstract: Long non-coding RNAs (lncRNAs) are reported to participate in tumor development. It has been manifested in previous researches that lncRNA ELFN1-AS1 is involved in early-stage colon adenocarcinoma with potential diagnostic value. However, no studies have revealed the specific mechanism of ELFN1-AS1 in colon cancer, and there are no other studies on whether ELFN1-AS1 is associated with tumorigenesis. In our study, ELFN1-AS1 with high expression in colon cancer was selected by TCGA analysis, and the survival ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…The above results appeared to support an existing viewpoint that ferroptosis is a type of autophagy-dependent cell death because a lot of autophagy-related signal pathways contributed to ferroptosis, including BECN1-mediated system xcinhibition and NCOA4-facilitated ferritinophagy (Song et al, 2018;Quiles Del Rey and Mancias, 2019;Zhou et al, 2020). ELFN1-AS1 was validated with high expression in colon cancer tissues and cells and was reported to promote proliferation and invasion of colon cancer cells by adjusting the miR-191-5p/SATB1 axis (Du et al, 2020). Liu et al (2020) suggested that VPS9D1-AS1 was a competing endogenous RNA in CRC cells and increased the expression of HMGA1, thereby influenced CRC progression.…”
Section: Discussionsupporting
confidence: 74%
“…The above results appeared to support an existing viewpoint that ferroptosis is a type of autophagy-dependent cell death because a lot of autophagy-related signal pathways contributed to ferroptosis, including BECN1-mediated system xcinhibition and NCOA4-facilitated ferritinophagy (Song et al, 2018;Quiles Del Rey and Mancias, 2019;Zhou et al, 2020). ELFN1-AS1 was validated with high expression in colon cancer tissues and cells and was reported to promote proliferation and invasion of colon cancer cells by adjusting the miR-191-5p/SATB1 axis (Du et al, 2020). Liu et al (2020) suggested that VPS9D1-AS1 was a competing endogenous RNA in CRC cells and increased the expression of HMGA1, thereby influenced CRC progression.…”
Section: Discussionsupporting
confidence: 74%
“…Cen investigated the impact of lncRNA IGFL2-AS1 in colon cancer, and the findings revealed that lncRNA IGFL2-AS1 increased colon cancer cell migration, proliferation, and invasion (Cen et al, 2021). Professor Du confirmed that the lncRNA ELFN1-AS1 promotes colon cancer cell proliferation and invasion by modulating the miR-191-5p/SATB1 axis in colon cells (Du et al, 2020). Progressively increasing research has demonstrated that lncRNAs have a crucial regulatory function in CC; however, the precise mechanism is still being debated.…”
Section: Analysis Of Qrt-pcrmentioning
confidence: 97%
“…ELFN1-AS1 can accelerate cell proliferation, migration, and invasion through regulating the miR-497-3p-CLDN4 axis in ovarian cancer ( 35 ). Furthermore, ELFN1-AS1 can promote cell proliferation and migration via the miR-191-5p –special AT-rich sequence-binding protein 1 axis in colon cancer ( 36 ). The exosome ELFN1-AS1 was shown to mediate M2 macrophage polarization to facilitate tumorigenesis in osteosarcoma ( 37 ).…”
Section: Discussionmentioning
confidence: 99%